Amniotic Epithelial Cells from the Human Placenta Potently Suppress a Mouse Model of Multiple Sclerosis - Liu, Yu Han; Vaghjiani, Vijesh; Tee, Jing Yang; To, Kelly; Cui, Peng; Oh, Ding Yuan; Manuelpillai, Ursula; Toh, Ban-Hock; Chan, James (PLOS ONE, 2012)
Human amniotic epithelial cells (hAEC) have stem cell-like features and immunomodulatory properties. Here we show that hAEC significantly suppressed splenocyte proliferation in vitro and potently attenuated a mouse model of multiple sclerosis (MS). Central nervous system (CNS) CD3+ T cell and F4/80+ monocyte/macrophage infiltration and demyelination were significantly reduced with hAEC treatment. Besides the known secretion of prostaglandin E2 (PGE2), we report the novel finding that hAEC utilize transforming growth factor-β (TGF-β) for immunosuppression. Neutralization of TGF-β or PGE2 in splenocyte proliferation assays significantly reduced hAEC-induced suppression. Splenocytes from hAEC-treated mice showed a Th2 cytokine shift with significantly elevated IL-5 production. While transferred CFSE-labeled hAEC could be detected in the lung, none were identified in the CNS or in lymphoid organs. This is the first report documenting the therapeutic effect of hAEC in a MS-like model and suggest that hAEC may have potential for use as therapy for MS.